THE UTILIZATION OF VILLAGE FUNDS IN VILLAGE DEVELOPMENT AND VILLAGE COMMUNITY EMPOWERMENT IN BUATA VILLAGE,BOTUPINGGE DISTRICT,BONE BOLANGO REGENCY - Sri Meilani Pakaya; Djamila Podungge; Mohamad Ikbal Kadir (Journal of Economic, Business, and Administration (JEBA), 2024)
This scientific paper aims to analyze the use of village funds in community development and eempowerment programs in Buata Village, focusing on the infrastructure and economic sectors. The research method used a descriptive qualitative approach. Data collection was carried out through in-depth interviews with key informants, as well as the study of related documents. Moreover, the data analysis used the Miles and Huberman model.The conclusion shows that the 2023 village fund allocation in Buata Village has been optimally utilized to fund several priority programs for village infrastucture development, such as improving road access, clean water, and drainage. Implementing these programs generally positivelly impacts accesbility, mobility, and villagers’ quality of life. However, using village funds in community economic empowerment is still insignificant in achieving the poverty alleviation target. This is because the program design is still not on target and is not supported by insentive follow-up assistance after training or capital assistance. Therefore, it is necessary to stengthen strategies and schemes so that similiar activities in the following years can run more optimally and substantially improve people’s welfare.